2019
DOI: 10.1097/md.0000000000014347
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid adenoma presenting with spontaneous cervical and anterior mediastinal hemorrhage

Abstract: Rationale: Spontaneous anterior cervical or mediastinal hemorrhage is a rare presentation of parathyroid adenoma. Patient concerns: A 69-year-old woman presented with neck hematoma and dysphagia and was found to have a soft tissue mass adjacent to her thyroid gland as seen on MRI and neck ultrasound. Diagnosis: Laboratory testing demonstrated elevated calcium and parathyroid hormone supporting diagnosis of parathyroid adenoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Since no unified diagnostic criteria in clinical practice, Simcic et al [ 7 ] had proposed three criteria for the diagnosis of parathyroid tumor rupture and bleeding: acute neck swelling, hypercalcemia, and neck or chest ecchymosis. Compared with imaging examination, not all cases meet the diagnostic criteria, the increase of blood calcium and PTH is more suggestive[ 1 , 3 , 8 ]. Hypercalcemia may be related to the release of cyst fluid containing high levels of parathyroid hormone caused by acute infarction of parathyroid adenoma, which also explains why the blood calcium and PTH of patients fall to normal levels soon after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since no unified diagnostic criteria in clinical practice, Simcic et al [ 7 ] had proposed three criteria for the diagnosis of parathyroid tumor rupture and bleeding: acute neck swelling, hypercalcemia, and neck or chest ecchymosis. Compared with imaging examination, not all cases meet the diagnostic criteria, the increase of blood calcium and PTH is more suggestive[ 1 , 3 , 8 ]. Hypercalcemia may be related to the release of cyst fluid containing high levels of parathyroid hormone caused by acute infarction of parathyroid adenoma, which also explains why the blood calcium and PTH of patients fall to normal levels soon after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat routine blood testing showed that the haemoglobin concentration had decreased from 124 g/L to 108 g/L in 8 h, suggesting active bleeding. Calcium concentration was 2.79 mmol/L (normal level, 2.25-2.75 mmol/L), parathyroid hormone (PTH) had been tested immediately which was 344.50 pg/mL (normal level, 15-65 pg/mL)[ 3 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…There are only about 100 cases reported with intracystic hemorrhage of parathyroid adenomas in the literatures. Some studies have shown that the use of anti-coagulation drugs ( 4 ) non-steroidal anti-inflammatory drugs ( 5 ) and trauma ( 6 ) may be risk factors; however, the cause of intracystic hemorrhage of parathyroid adenomas is unknown. It is currently believed that if tumor growth is too rapid and the blood supply to the tumor is insufficient, hemorrhage of parathyroid adenomas may occur ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…After performing a literature search of PubMed and Google Scholar databases, thirty cases of spontaneous haemorrhage in parathyroid adenomas were identified, with only one previous report of spontaneous haemorrhage in a parathyroid carcinoma . Our case report was assembled following CARE case report guidelines, with written informed consent obtained from the patient and the Institutional Review Board according to the Helsinki Declaration of 1983.…”
mentioning
confidence: 99%
“…An added difficulty is distinguishing between thyroid and parathyroid involvement, even with available CT and US findings. Neck haematomas associated with parathyroid carcinomas are extremely rare and should be considered when the patient has dysphagia, cervical or thoraco‐cervical ecchymoses and hypercalcaemia, alongside a firm parathyroid mass …”
mentioning
confidence: 99%